Testy psychologiczne w badaniach glottodydaktycznych - Małgorzata Kolera, Małgorzata Kolera (Neofilolog, 2010)
This paper presents the possibilities and limitations of using psychological tests in glottodidactics. After a brief presentation of psychological variables that can be measured in glottodidactic research and specifying the concept of these tests and their psychometric quality criteria, the restrictions on their use by non-psychologists are revealed. The article focuses on analysing the core psychological and psychometric knowledge and skills that are essential for competent selection, administration and interpretation of such tests and that limit test access to qualified individuals as well as protect the instruments from misuse. Finally, some options for cooperation with qualified psychologists are suggested, to show the way for responsible and competent use of psychological tests in glottodidactics.